2004
DOI: 10.1002/pmic.200300797
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 27 in human renal cell carcinoma

Abstract: Heat shock protein 27 (HSP27, Swiss-Prot accession number P04792) is a component of the large and heterogeneous group of chaperone proteins, and its main functions are inhibition of apoptosis and prevention of aggregation of actin intermediate filament. Modified expression of HSP27 has been described in several cancers including testis, breast, and ovaric cancer. In the present work, 18 renal cell carcinoma (RCC) tissues and homologous normal kidney tissues have been investigated for HSP27 expression by combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 22 publications
6
66
1
Order By: Relevance
“…Previous 2D gel electrophoresis studies of heart tissues and cell lines reported largely diversified results for the number of HSP27 spots. Depending on the cell type, the number of isoforms with different phosphorylation status varied from 2 to 80 (10,42,44,47). Especially in pathogenic tissues, increased numbers of HSP27 spots have been observed in 2D gels, likely because of disintegration of HSP27 oligomers and also different degrees of phosphorylation, such as, for example, mono-, di-, and triphosphorylation.…”
Section: Attenuation Of Dox-induced Apoptosis In Heat-shocked Cardiacmentioning
confidence: 99%
“…Previous 2D gel electrophoresis studies of heart tissues and cell lines reported largely diversified results for the number of HSP27 spots. Depending on the cell type, the number of isoforms with different phosphorylation status varied from 2 to 80 (10,42,44,47). Especially in pathogenic tissues, increased numbers of HSP27 spots have been observed in 2D gels, likely because of disintegration of HSP27 oligomers and also different degrees of phosphorylation, such as, for example, mono-, di-, and triphosphorylation.…”
Section: Attenuation Of Dox-induced Apoptosis In Heat-shocked Cardiacmentioning
confidence: 99%
“…Previous studies have shown higher expression of HSP27 in ccRCC (27,(29)(30)(31)(32). We observed the same result.…”
Section: Discussionsupporting
confidence: 82%
“…The most acidic of the five isoforms of Hsp27 was detected almost exclusively in infected cells, indicating that PrV infection caused a sharp rise in these isoforms. Most probably, the charge variants are the result of differential phosphorylation, which was previously described for human (37,48) and bovine (28) Hsp27. A similar shift to higher phosphorylated forms of Hsp27 has been observed after treatment of bovine cells with cadmium (28), indicating that this reaction is not specific for infections with herpesviruses but rather reflects phosphorylation of Hsp27 during cellular stress (27).…”
Section: Discussionmentioning
confidence: 99%